Patient involvement in healthcare workers' practices: how does it operate? A mixed-methods study in a French university hospital - Lucie Malloggi; Brice Leclère; Clément Le Glatin; Leïla Moret (BMC, 2020)
Abstract Background The present challenge for patient involvement is the improvement of healthcare efficiency through a deeper consideration of the patient experience. In hospitals, numerous interventions promoting patient involvement are informally implemented by healthcare workers (HCWs). The first aim of this study was to conduct an overview of hospital HCWs' experiences of the involvement of patients or their representatives. This overview included the involvement of patients in the domains of healthcare provision and support for other patients, healthcare quality and safety improvement, training and research. The second aim was to describe the challenges and conditions for the development of participative interventions by HCWs. Methods We conducted a mixed-methods sequential study at Nantes University Hospital from September 2017 to May 2018. To achieve the first aim, we performed a descriptive analysis of quantitative data collected via a questionnaire survey of 1290 HCWs. To achieve the second aim, we conducted a thematic analysis of qualitative data collected via eight semi-structured interviews with HCWs who reported involving patients or their representatives (family and patient association members) in healthcare. Results Among the 213 survey participants (16.5%), 133 reported a total of 424 participative interventions, mostly in the domains of care quality and safety (37%) and care provision and support (29%). The analysis of the qualitative data evidenced three types of factors determining the implementation of such interventions: the profiles of patients and their representatives, the beliefs and attitudes of HCWs, and organisational factors. While leadership from patients and HCWs was a central element in the development of patient involvement interventions, organisations' capacities to foster a sustainable partnership culture appeared to be the next challenge to promote the patient-as-partner model in health systems. Our results also highlighted numerous benefits of patient and representative involvement for patients and HCWs. Conclusions The numerous initiatives reported show that patients and patient representatives participate alongside HCWs in hospitals. It is essential to take into account the facilitating and hindering factors of patient involvement in hospital HCWs' practices for the further development of current initiatives. Additional studies, especially from the point of view of patients, are needed to complement our findings.